Bio-derived materials as a green route for precious & critical metal recovery and re-use. Issue 4 (5th February 2015) - Dodson, Jennifer R.; Parker, Helen L.; Muñoz García, Andrea; Hicken, Alexandra; Asemave, Kaana; Farmer, Thomas J.; He, He; Clark, James H.; Hunt, Andrew J.
Abstract : Overview of research in critical and precious metal recovery using biosorption, application to real-life wastes and uses of the metal-loaded materials. Abstract : To meet the global challenges of elemental sustainability a holistic approach to the extraction, use and recovery of precious and critical metals must be developed. Biosorption is a key technology for the benign recovery of diffuse elements from liquid effluents and hydrometallurgy processes. There is the opportunity to go beyond the remediation of heavy metals and pollutants, by utilising biosorption within a circular economy approach for the cycling of precious and critical metals in higher-value applications. This review provides an overview of the current research in the area of critical and precious metals recovery using biosorption, its application to real-life wastes and the potential uses for these metal-loaded materials for catalysis or functional materials.